What Is the Impact of Automated Synovial Cell Counting on Different Aseptic Causes and Periprosthetic Conditions Associated With Revision THA?. Issue 5 (1st May 2022) - Abdelaziz, Hussein; Aljawabra, Alaa; Rossmann, Markus; Tien, Calvin Shum; Citak, Mustafa; Klatte, Till Orla; Gehrke, Thorsten
Abstract: Background: Studies have suggested that automated synovial cell counting may overestimate the white blood cell (WBC) count, resulting in false positive tests when evaluating patients for the possibility of periprosthetic joint infection (PJI) after THA. However, associations between WBC counts high enough to mimic PJI in patients whose arthroplasties are not infected but rather are experiencing a variety of aseptic problems—including but not limited to metallosis, polyethylene wear, and recurrent dislocation—have not, to our knowledge, been adequately addressed. In addition, there is a lack of analyses about the polymorphonuclear percentage (PMN%) when assessed by automated analyzers in this context. Questions/purposes: In the context of different indications for aseptic revision and different periprosthetic hip pathologic findings, we asked: (1) What were the synovial WBC count levels, and what proportion of values were above the 2018 International Consensus Meeting (ICM) cutoff (3000 cells/μL)? (2) What were the synovial PMN% levels, and what proportion of values were above the 2018 ICM (70%)? Methods: We retrospectively studied the preoperative cell count analyses of synovial fluid in patients who underwent revision THA for aseptic reasons at our tertiary referral arthroplasty center between January 2015 and December 2017. We considered all revisions performed on patients during that time potentially eligible, and after prespecified exclusions were applied (exclusions mainly included 15% [197 of 1306] sporadic missing data and 12% [155 of 1306] insufficient synovial fluid obtained in the aspirate), a total of 702 patients undergoing revision THA for aseptic reasons remained for the final analysis. As far as we know, no patients underwent re-revision for PJI at a mean follow-up of 46 ± 11 months, which tends to confirm our impression that indeed these hips did not have PJI. Cell count analyses were conducted using an automated analyzer. Clinical findings, preoperative radiographs, and surgical reports––confirmed by available histologic results––were used to establish diagnoses. We evaluated these hips considering the recommendations of the 2018 ICM (WBC count of 3000 cells/μL and PMN% of 70%) to see what proportion of them would have been characterized as likely having PJI on basis of those cutoff values. The mean WBC count for the entire cohort was 2120 ± 2395 cells/μL. The mean PMN% for the entire cohort was 36% ± 22%. Results: Compared with aseptic loosening and recurrent dislocation, polyethylene wear had the highest mean WBC count (3817 ± 3711 cells/μL; p < 0.001). Of the investigated periprosthetic conditions, wear-induced synovitis had the highest value (4464 ± 3620 cells/μL; p < 0.001). Considering the ICM threshold, polyethylene wear showed the highest proportion of WBC counts above 3000 cells/μL among the indications for aseptic revision (60% [25 of 42]; p < 0.001). Of the periprosthetic conditions, wear-induced synovitis showed the highest proportion beyond the ICM cutoff (60% [50 of 83]; p < 0.001). The mean PMN% for aseptic causes ranged between 28% and 44% without differences among them (p = 0.12). Patients with metallosis had the highest mean PMN% of the periprosthetic conditions investigated (45% ± 25%; p = 0.007). Regarding the ICM threshold, metallosis resulted in the largest proportion of patients with a PMN% above 70% (21% [10 of 47]; p = 0.003), and that for wear-induced synovitis was 6% (5 of 83; p = 0.42) and for osteolysis was 3% (1 of 33; p = 0.51). There were no differences among aseptic loosening, recurrent dislocation, and polyethylene wear in terms of the proportion above 70% among the aseptic revision causes. Conclusion: Using automated cell counting, we found that WBC counts differ widely across indications for aseptic revision THA, and a high proportion of patients who underwent revision THA for aseptic reasons had WBC counts above the commonly used threshold of 3000 cells/μL. However, the PMN% was much less affected in several common indications for aseptic revision THA, making this measure more reliable for interpreting aspiration results using an automated analyzer. Based on the data distributions we observed, manual counting techniques might be considered in particular among patients with polyethylene wear, metal-on-metal bearing surfaces, or suspected metallosis. However, an elevated WBC count alone, observed using an automated analyzer in the context of polyethylene wear, should not be considered to be strongly suggestive of PJI, since that finding occurred so commonly among patients without infection. Level of Evidence: Level III, diagnostic study.